Pengaruh Motivasi Kerja, Komunikasi Dan Stres Kerja Terhadap Kinerja Karyawan (Studi Pada CV. Fara Collection) - Adhi Widyakto; Nur Kholifah; Rr Lulus Prapti NSS; Dian Triani (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to test empirically the analysis of the effect of work motivation, communication and work stress on the performance of employees of CV. Fara Collection. The population of this research is all employees of CV. Fara Collection. The sample used in this study were 88 respondents. In this study using census techniques, namely where the number of samples is the same as the population. Then the data collection method was through questionnaires and data analysis using SPSS data which included validity, reliability, classic assumption tests, multiple regression analysis, hypothesis testing using the t test and R2 test. The results of this study indicate that all independent variables, namely work motivation, communication and work stress have a positive and significant effect on employee performance (Y) partially or simultaneously (together). Based on the coefficient of determination of 0.597, which means that 59.7 percent of employee performance variables can be explained by the variables of work motivation, communication and work stress while the remaining 40.3 percent is explained by other variables outside this study.